2011
DOI: 10.1097/mot.0b013e328346dd36
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant in Jehovah's Witnesses patients

Abstract: In summary, major surgery can be performed safely in the Jehovah's Witness who refuses blood transfusion by utilizing preoperative and intraoperative techniques that decrease surgical blood loss, decrease oxygen consumption, and increase oxygen delivery. Even if significant intraoperative blood loss occurs, successful postoperative management is possible by utilizing techniques that minimize oxygen consumption and maximize oxygen delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Uncontrolled bleeding leads to a combination of haemodilution, hypothermia, consumption of clotting factors, reduced oxygen delivery to tissues and resultant acidosis, which in turn exacerbates the clotting process further causing a vicious ‘bloody' circle. With advances in anaesthetic and surgical techniques, development of newer parenchymal transaction devices, vessel control instruments and haemostatic adjuncts, it should be possible to perform major liver resections and liver transplantation with minimal or no transfusion even in Jehovah's Witness patients [10,11,12]. With increasing safety, mortality rates as low as 1-2% in specialist centres have been reported [13].…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled bleeding leads to a combination of haemodilution, hypothermia, consumption of clotting factors, reduced oxygen delivery to tissues and resultant acidosis, which in turn exacerbates the clotting process further causing a vicious ‘bloody' circle. With advances in anaesthetic and surgical techniques, development of newer parenchymal transaction devices, vessel control instruments and haemostatic adjuncts, it should be possible to perform major liver resections and liver transplantation with minimal or no transfusion even in Jehovah's Witness patients [10,11,12]. With increasing safety, mortality rates as low as 1-2% in specialist centres have been reported [13].…”
Section: Introductionmentioning
confidence: 99%
“…Few case reports and case series have suggested that the use of CS might increase the risk of acute respiratory distress syndrome, acute renal failure or disseminated intravascular coagulopathy due to debris released from salvaged erythrocytes [8]. This has not been confirmed in a subsequent study [44]. Another potential risk associated with CS is the bacterial contamination of blood suctioned from the surgical field.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 64%
“…Another potential risk associated with CS is the bacterial contamination of blood suctioned from the surgical field. The above-mentioned study showed that despite the fact that blood washing was not able to eliminate all bacterial contamination, autotransfusion of salvaged blood, was not associated with an increased rate of positive blood cultures and risk of postoperative infections [44]. To minimize the risk of bacterial contamination it is recommended to start collecting blood after the removal of ascitic fluid and cease it once biliary anastomosis begins [34].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…With the improvement of surgical techniques and anesthesia practices, the amount of blood transfused has been dramatically reduced [1][2][3]. Some centers achieved avoidance of RBC transfusion in up to 40% of liver recipients [4][5][6][7], and bloodless OLT has been reported in single cases and case series [8][9][10][11][12][13][14][15][16]. Also contributing to this trend is the increasing awareness of the hazards associated with blood transfusion in OLT [4,17,18], which have been observed in patients receiving red blood cells, platelets and plasma products [17,19,20].…”
Section: Introductionmentioning
confidence: 97%
“…The former presents a unique ethical dilemma in Jehovah's Witnesses patients, who on the basis of religious beliefs refuse transfusion of blood products [8][9][10][11][12][13][14][15][16]21]. The reliance on blood transfusion may also delay OLT in patients with numerous red blood cell alloantibodies or with deficiencies in IgA or haptoglobin [22,23].…”
Section: Introductionmentioning
confidence: 99%